SEXUAL VIOLENCE IN MARRIAGE (MARITAL RAPE): A FIQH PERSPECTIVE AND THE SEXUAL VIOLENCE CRIMES LAW (UU TPKS) - Ainul Mardhiah; Muhammad Syahnan; Muhammad Iqbal Irham (Program Pascasarjana UIN Sumatera Utara, 2026)
The phenomenon of forced sexual relations against wives within marriage is an issue that has sparked debate in contemporary Fiqh and the Sexual Violence Crimes Law (UU TPKS). This research aims to explain the opinions of scholars found in contemporary fiqh literature concerning husband-wife relationships and compare them with the sexual violence crimes law. This paper is intended to find the correlation between the perspectives of contemporary scholars and the UU TPKS regarding sexual violence in marriage and the concept of a wife's obedience to her husband in Islam. The research employs a qualitative method with a juridical-normative approach, drawing from contemporary fiqh books, Ahwal Syakhsiyyah, and the sexual violence crimes law. The findings of this research indicate that fiqh law is essentially in alignment with the concept of sexual violence law in marriage as outlined in the UU TPKS. Conversely, the stance of rejection towards the UU TPKS is shown to be a result of misunderstandings of existing religious texts.